Winged beans in Zaire - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
A Belgian agronomist and author,Jean-Pierre Hallet, has introduced the South-East Asian winged bean into Zaire.